Thermal and energy performance of green roof and cool roof: A comparison study in Shanghai area - He, Yang; Yu, Hang; Ozaki, Akihito; Dong, Nannan (Journal of Cleaner Production, 2020)
Green roofs and cool roofs are commonly used to improve indoor thermal environment, reduce air-conditioning load and mitigate the Urban Heat Island (UHI) effect. This study aimed to quantify the differences in thermal and energy performance between the two different roof types under the climate of Shanghai. Firstly, field experiment was conducted in the Shanghai area. Thermal performance of green roof, cool roof and common roof in summer and winter were measured. Results showed that, compared to common roof, the cool roof had an average cooling effect of 3.3 °C on the outer roof deck surface in summer, while the green roof only had a cooling effect of 2.9 °C. In winter, the green roof provided good insulation, and could improve outer surface temperature of the roof deck by an average of 3.3 °C compared to the cool roof. A hygrothermal transfer model for green roof was coupled with a dynamic building thermal performance simulation software (THERB) and validated using measured data. The coupled model was used to predict the effect of both roof types on energy performance of a public building. Simulation results showed that green roof could reduce the cooling and heating loads of the top floor by 3.6% and 6.2%, respectively. The cool roof could reduce cooling load by 3.6% and increase heating load by 10.4%. Finally, a parametric analysis was implemented. The functional mechanism of the main parameters of green and cool roof as well as their impacts on thermal and energy performance of public buildings were analyzed in detail. Conclusions drawn from this paper could provide guidance for the design optimization and application of green roof and cool roof in Shanghai area. •Thermal performance of green roof and cool roof was monitored in Shanghai area.•A green roof heat transfer model was coupled with BES model (THERB) and validated.•Thermal and Energy effect of green and cool roof on public building was predicted.•Parametric analysis on thermal and energy performance of green roof was conducted.•Parametric analysis on thermal and energy performance of cool roof was conducted.